Pengaruh Dukungan Sosial dan Adversity Quotient terhadap Future Anxiety pada Mahasiswa - Aulia Maharani Elsafir; Agus Salim; Zahro Varisna Rohmadani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of social support and adversity quotient on future anxiety in students. The subjects in this study are 200 students in the province of DI Yogyakarta. The research sampling technique is random sampling, with samples selected at random, regardless of strata in the population. The instruments used in this study used future anxiety scales with a reliability value of 0.915, social support scales with a reliability value of 0.910 and adversity quotient scales with a reliability value of 0.876. The data analysis technique used is multiple linear regression analysis using IBM SPSS Statistics 25. The results of the study revealed that the average student experienced moderate future anxiety, and there was a significant influence between social support and adversity quotient on future anxiety in students. Social support and adversity quotient for future anxiety provided an effective contribution of 10.2% with a value of P =.102. While the remaining 89.8 was influenced by other factors such as internal factorcs from oneself.